Financial crisis in the Philippines - Oh, Chee Sien (2008)
There were 4 main points. Firstly,underlying causes of the crisis, secondly, a comparative study to Thailand and Indonesia, thirdly, policies responses by the government and IMF, and lastly, lessons learnt were highlighted.